Influence of Mannan oligosaccharides and Tulasi (ocimum sanctum) on Carcass and Meat Quality Characteristics of Rabbits - Khadeer, B S; Reddy, L S S V Prasad; Reddy, G V Bhaskar; Kumar , A V N S; Naik , B R (Journal of Meat Science, 2023)
The present experiment was conducted with twenty-four Newzealand white male rabbits weighing around 580 g that were assigned into four homogeneous treatment groups randomly (C, T1, T2 and T3) each with six rabbits. The rabbits fed with basal diet (without any antibiotic, coccidiostat or growth promoting supplements) grouped as control; basal diet mixed with the prebiotic (MOS) @ Mannan oligo saccharide (1.0 g/ kg feed) grouped as T1; basal diet mixed with the antibiotic ie) Oxytetracycline hydrochloride powder @ 250 g/tone of feed are grouped as T2 and basal diet mixed with the herbal powder tulasi (Ocimum sanctum) leaf powder @ 50g/kg feed are grouped as T3 and the trail was conducted for a period of 42 days. Rabbits fed with tulasi (Ocimum sanctum) leaf powder (TLP) @ 50g/kg feed had significantly (P0.05) influenced the carcass length of rabbits. Addition of tulasi leaf powder in the rabbit diet significantly (P
Keywords: Rabbits; Prebiotics; Tulasi leaf powder; Carcass characteristics; Meat quality attributes